Incidence of Surgical Glove Perforations during Surgical Procedures at a Tertiary Care Hospital, Islamabad - Hina Idrees; Isbah Rashid; Muhammad Aqib; Sajid Ali Shah; Sana Sharafat Ali; Muhammad Faheem Ahsan; S H Waqar (Life and Science)
Objective: To determine the rate and patterns of surgical glove perforation during surgical procedures and to compare the rates between emergency and elective surgeries at PIMS, Islamabad. Study Design:  A cross-sectional study. Place and Duration of Study: The study was conducted in the Department of General Surgery of Pakistan Institute of Medical Sciences (PIMS), Islamabad, Pakistan from January 2021 to June 2021. Materials and Methods: Surgical gloves are worn in various major surgeries, elective and emergency, and were studied post-procedure, for six months’ period. Gloves were examined by standardized visual and hydro-insufflation techniques to check for perforations. Glove quality was also noted. The type of procedure carried out, the number of perforations, the location of perforations, and the roles of the surgical team were all recorded along with other relevant information. Data were analyzed using SPSS version 22. Results: A total of 120 gloves were tested perforated, 69/100 for elective and 51/80 for emergency procedures. Perforations in emergency procedures were 57.5% ±0.44, while 42.5% ±0.52 in elective surgeries. Glove perforations were extremely common among first assistants (26.67%) and second assistants (9.17%) during emergency surgeries as well as among first surgeons (30%) and scrub nurses (11.67%) during elective procedures. Only 1.2% of inner glove perforations were recorded. The most commonly perforated parts of the glove were the left hand, the left index finger and the thumb. Residents had a lower rate of glove perforation than consultant surgeons. Conclusion: Calculated perforation rate is high, posing a clear threat to the surgical workforce. Preventive measures such as double gloving should be routinely adopted for all surgical procedures. Glove quality is also an important contributing element.